Penerapan Media Pembelajaran Audio Visual Pada Mata Pelajaran PJOK Di Sekolah Dasar - Annisa Nurdianti; Danang Dwi Basuki (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2023)
Education is very important in the lives of students. Education is very closely related to the learning process because students get a change. So it is important for teachers to improve skills and use appropriate methods and media in learning. This study aims to describe the use of Audio Visual media in PJOK learning. Because the use of Audio Visual media is a strategic way to improve student learning outcomes because the audio visual media in it displays attractive sound and display images so as to stimulate students' sight and hearing. The focus of this research is (1) what media are used by PJOK teachers during the learning process? (2) is learning using Audio Visual effective? (3) Is there a change in students' ability to learn after the teacher teaches using audio-visual media? (4) Are there any obstacles when using Audio Visual media in the learning process? This research is qualitative in nature and data collection techniques are observation and interviews. audiovisual like youtube. (2) learning using audio-visual media is very effective in elementary schools. (3) students' learning abilities increase when using audio-visual media (4) the obstacles faced by PJOK teachers when using Audio Visual are network constraints